Total Block Edge Cut Vertex Graph - Goudar, Venkanagouda M (International Journal of Applied Mathematical Research, 2012)
In this paper, we introduce the concept of the total block edge cut vertex graph. We obtain some properties of these graphs. We present characterization of graphs whose block edge cut vertex graphs planar outer planar, minimally non outer planar and crossing number one.